Self-concept explains gender differences in mental rotation performance after stereotype activation - Rahe, Martina; Schürmann, Linda; Jansen, Petra (Frontiers in Psychology, 2023)
Mental rotation is an ability that usually displays robust and large gender differences in favor of boys and men. When participants are told that males outperform females, it can result in worse performance for females (stereotype threat effect) and better performance for males (stereotype lift effect). Because various studies show different results for the effect of stereotype activation, the present study aimed to investigate whether adolescents’ self-concept would moderate stereotype activation effects. Therefore, 127 adolescents (61 male, 66 female) between 10 and 18 years (M = 13.54, SD = 1.99) solved the mental rotation test and filled out a questionnaire about their perceived performance, stereotype beliefs, and self-concept. Results showed that self-concept and stereotype activation affected male and female adolescents’ actual and perceived performance differently. For males, a better self-concept was associated with better performance in adolescents with stereotype activation and with lower performance in those without the activation. This interaction was only marginally significant. For females, an increasing self-concept was associated with worse performance in adolescents with stereotype activation and with better performance in those without activation. Furthermore, a better self-concept was associated with higher perceived performance in male adolescents with stereotype activation and with lower perceived performance without the activation. Reasons for these results could be the (in)congruence between males’ own perception of their abilities (self-concept) and the instruction of the activation.